LOT RELEASE COST ACCOUNTING IN THE AVIATION INDUSTRY. - Smith, Frank P. (The Accounting Review, 1947)
Companies in the aviation industry, particularly those manufacturing or assembling airplanes and major subassemblies, have adapted to their use a job-lot type of cost accounting based on specific numbers of planes or parts in a "lot" or "release." During the recent war period an individual lot might represent hundreds of units costing many millions of dollars. Production of such magnitude will probably not be required in the postwar years, but the cost procedures developed for such production can be utilized to meet current accounting requirements. The lot or release system of determining costs of airplanes is becoming increasingly important as a result of the inclusion of price redetermination provisions in many government contracts. Such provisions are of many different types. In some cases the price of a plane or part is redetermined at completion of a specific number of units; in some cases a particular item of cost, for example, overhead, is redetermined at a specific point of time; in other cases the price is redetermined at completion of a specified percentage of an entire contract. All redetermination provisions are intended to provide for the renegotiation of price, or types of cost, on the basis of actual experience. This is likely to be of particular significance during the years immediately ahead as companies in the aviation industry undertake to produce new types of planes and to meet specifications and tests undreamed of in the prewar years.